Preliminary estimate of the impact of support structures on the aerodynamic performance of very large wind farms - Ma, L; Nishino, T (IOP Publishing, 2018)
An extended theoretical model, which is based on a two-scale coupled momentum conservation argument, is proposed to estimate aerodynamic effects of support structures on the performance of ideal very large wind farms. A key implication of this extended model is that the parameter (As/A)·CD* where A and As are the rotor swept area and support-structure frontal projected area, respectively, and CD* is an effective support-structure drag coefficient, plays an important role in the design of very large wind farms. In particular, the optimal farm density tends to decrease as the normalised support-structure drag increases. To validate this extended model, Wall-Modelled Large-Eddy Simulations (WMLES) of a periodic array of actuator discs with and without support structures are conducted; results agree qualitatively with the model.